SDS-PAGE and enzyme immunoassay methods for detection of porcine gelatin in edible bird's nest - Tukiran, Nur Azira; Mohamed Roslan, Nur Illiyin; Ismail, Amin (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
Porcine gelatin is one of the common adulterant found in processed edible bird’s nest (EBN); as to increase its net weight prior to sale. This study aimed to develop a sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) and an enzyme immunoassay method to detect the presence of porcine gelatin in processed EBN. SDS-PAGE method was developed by comparing the polypeptide patterns of porcine gelatin with the EBN. In the evaluation of the spiked samples of 2.5% to 50% (v/v), SDS-PAGE was able to detect 20% of porcine gelatin in EBN. An indirect enzyme linked immunosorbent assay (ELISA) was then developed for detection of lower amounts of porcine gelatin. A polyclonal rabbit antibodies was raised against the species-specific sequence of porcine collagen alpha 2 (I) chain. The detection limit for porcine gelatin was 0.05% in EBN. This ELISA is suitable for monitoring of EBN’s quality and purity in the supply chain.